2021
DOI: 10.3390/antiox11010030
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NOX5 Expression Modulates Thermogenesis and Lipolysis in Mice Fed with a High-Fat Diet and 3T3-L1 Adipocytes through an Interleukin-6 Dependent Mechanism

Abstract: Obesity is a global health issue associated with the development of metabolic syndrome, which correlates with insulin resistance, altered lipid homeostasis, and other pathologies. One of the mechanisms involved in the development of these pathologies is the increased production of reactive oxygen species (ROS). One of the main producers of ROS is the family of nicotinamide adenine dinucleotide phosphate (NADPH) oxidases, among which NOX5 is the most recently discovered member. The aim of the present work is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Moreover, they had lower glycaemia, and improved insulin-induced glucose uptake [ 37 ]. In an additional study we found that in these mice NOX5 promoted the expression and activation of specific thermogenesis and lipolysis markers at mesenteric and epididymal fat [ 38 ]. Other groups have recently linked NOXes, and more specifically NOX5, with metabolism alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they had lower glycaemia, and improved insulin-induced glucose uptake [ 37 ]. In an additional study we found that in these mice NOX5 promoted the expression and activation of specific thermogenesis and lipolysis markers at mesenteric and epididymal fat [ 38 ]. Other groups have recently linked NOXes, and more specifically NOX5, with metabolism alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress in accumulated fat is an important pathogenic mechanism of obesity-associated metabolic syndrome [ 35 , 36 , 37 ]. ROS production was selectively increased in the adipose tissue of obese mice, accompanied by increased NADPH oxidase expression and decreased antioxidant oxidase expression [ 38 , 39 ]. The NADPH oxidase NOX4 is a hydrogen peroxide (H 2 O 2 )-producing enzyme [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, applying conditional media from NOX5-expressing endothelial cells on 3T3-L1 adipocytes led to reduced lipid accumulation and increased glucose uptake [ 61 ]. The same group reported that NOX5 expression in obesity led to elevated interleukin (Il-6) production, which results in upregulated thermogenesis and lipolysis in adipose tissue via upregulation of Pgc1α and Ucp1 expression [ 62 ].…”
Section: Nadph Oxidases and Obesitymentioning
confidence: 99%